An - Whitmore, T.C. (Oxford University Press, 1998)
The book remains unique in linking rain forest biology and ecology with silviculture, and with concerns over sustainable resource utilization and the future of the tropical rain forests. It includes sections on the diverse animal and plant life forms which are found in the rain forest, and the interconnections between them. Nutrient cycles and forest dynamics are fully explained, with new data on ecophysiology and forest microclimates